Early Childhood Sexual Education in Preventing Sexual Violence at Kasih Yobel Christian Kindergarten and Generasi Unggul Christian Kindergarten in Kupang City - Fenta Imelda Solle; Vanida Mundiarti; Sartika Kale (Universitas Nusa Cendana, 2024)
The rise in cases of sexual violence against minors is very worrying. The aim of the research is to describe how to plan, implement and evaluate sex education at the Kasih Jubilee Christian Kindergarten and the Generation Superior Christian Kindergarten in Kupang City. The research uses a descriptive qualitative approach. Data was collected using interviews and documentation. The validity of the data uses triangulation and is analyzed using the Miles and Huberman interactive model. The research results show that; Teacher planning uses the 2013 curriculum as a guide in preparing RPPM/RPPH, preparing laptop media, speakers, LCD and children's worksheet books. The implementation of sex education is centered on children and teachers where teachers teach gender differences, body parts and their functions, maintaining personal hygiene, knowing what touch is allowed and what is not allowed, and what to do if someone tries to hold it. This is delivered using singing, question and answer, puzzle methods. , lectures, coloring, collage, and role playing. Evaluation uses anecdotal notes, checklists and children's work.